Influence of foliar and soil potassium fertilizer on ratoon sugarcane performance: yield, quality, and nutrient uptake - Khontiang, Kamonrat; Ketrot, Daojarus; Tawornpruek, Saowanuch; Wongleecharoen, Chalermchart; Inboonchuay, Tawatchai; Wongsuksri, Acharaporn (Frontiers in Soil Science, 2025)
Potassium (K) is essential for optimizing sugarcane production, playing a critical role in various processes that influence yield and quality. However, the effectiveness of different K forms in enhancing sugarcane productivity through foliar application remains underexplored, leaving a significant knowledge gap. This study investigates the impact of various foliar K supplements under differing soil K conditions, hypothesizing that such supplementation will enhance yield and nutrient uptake in ratoon sugarcane. Field trials were conducted on first ratoon sugarcane in loamy soil, using a 2 × 7 factorial in a randomized complete block design. The first factor compared no soil-applied K with soil-applied K, while the second factor consisted of foliar K treatments: water (control), 2.5% weight by volume of KCl, K₂SO₄, K₂SiO₃, KNO₃, diluted molasses, and vinasse at a 5× dilution. Results indicated that foliar supplementation with KNO₃ and K₂SiO₃ (without soil-applied K) effectively maintained ratoon sugarcane yield and sugar yield, comparable to yields achieved with soil-applied K combined with foliar water. Foliar K supplementation also improved the uptake of N, P, K, and Si in cane stalks, matching or exceeding uptake levels observed in ratoon sugarcane with soil-applied K. Although no yield enhancement was observed with the combination of foliar K supplementation and soil-applied K, most foliar K treatments increased K uptake even with adequate soil K levels. In conclusion, foliar K supplementation, particularly with KNO₃ and K₂SiO₃, is an effective strategy for maintaining sugarcane productivity, and improving nutrient use efficiency, especially when K fertilizer is unavailable or costly.